2021
DOI: 10.3389/fitd.2021.778724
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Preclinical Platforms of Loa loa for Filarial Neglected Tropical Disease Drug and Diagnostics Research

Abstract: The tropical disease, loiasis, caused by the filarial parasite, Loa loa, has gained prominence in global public health as a cause of excess mortality and a barrier to the elimination of the related prioritized neglected tropical diseases (NTDs), lymphatic filariasis and onchocerciasis, within Central Africa. There are no effective drug cures or vaccines available to treat loiasis safely. Here we review recent advances in loiasis preclinical platform technologies, including novel in vitro culturing systems, ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…To assess the potential use of PVP, THP and 06 in countries co-endemic for Loa loa, further in vitro studies are necessary to determine the IC 50 s of these compounds with mf, as well as validating the potency of these compounds on the mf in animal models [28].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the potential use of PVP, THP and 06 in countries co-endemic for Loa loa, further in vitro studies are necessary to determine the IC 50 s of these compounds with mf, as well as validating the potency of these compounds on the mf in animal models [28].…”
Section: Discussionmentioning
confidence: 99%
“…Since no L3 could be recovered from M. perstans and O. volvulus inoculated mice, we were wondering if the isolated L3 were suitable for mouse infection experiments. However, previous studies showed that immunocompromised mice were susceptible to Loa loa L3 (27)(28)(29). Thus, we isolated Loa loa L3 from engorged Chrysops flies to inoculate the different immunocompromised mice with Loa loa L3.…”
Section: Parasite Recovery Ratesmentioning
confidence: 98%